Metallaphotoredox‐Enabled Intermolecular Carbobromination of Alkynes with Alkenyl Bromides. Issue 7 (8th March 2022) - Yu, Wei; Jiao, Xiaorui; Fan, Yanmin; Zhu, Shengqing; Chu, Lingling
Abstract: A regioselective intermolecular carbohalogenation of alkynes with alkenyl bromides enabled by dual photoredox and nickel catalysis is described. This dual protocol enables an atom‐economic access to a wide array of brominated 1, 3‐dienes from simple starting materials. Broad substrate scope and high regioselectivity are observed. The synthetic utility has been demonstrated and preliminary mechanistic studies have been performed to elucidate the reaction pathway. Abstract :